Inconsistent use of gesture space during abstract pointing impairs language comprehension - Gunter, Thomas C.; Weinbrenner, J. E. Douglas; Holle, Henning (Frontiers in Psychology, 2015)
Pointing toward concrete objects is a well-known and efficient communicative strategy. Much less is known about the communicative effectiveness of abstract pointing where the pointing gestures are directed to “empty space.” McNeill's (2003) observations suggest that abstract pointing can be used to establish referents in gesture space, without the referents being physically present. Recently, however, it has been shown that abstract pointing typically provides redundant information to the uttered speech thereby suggesting a very limited communicative value (So et al., 2009). In a first approach to tackle this issue we were interested to know whether perceivers are sensitive at all to this gesture cue or whether it is completely discarded as irrelevant add-on information. Sensitivity to for instance a gesture-speech mismatch would suggest a potential communicative function of abstract pointing. Therefore, we devised a mismatch paradigm in which participants watched a video where a female was interviewed on various topics. During her responses, she established two concepts in space using abstract pointing (e.g., pointing to the left when saying Donald, and pointing to the right when saying Mickey). In the last response to each topic, the pointing gesture accompanying a target word (e.g., Donald) was either consistent or inconsistent with the previously established location. Event related brain potentials showed an increased N400 and P600 when gesture and speech referred to different referents, indicating that inconsistent use of gesture space impairs language comprehension. Abstract pointing was found to influence comprehension even though gesture was not crucial to understanding the sentences or conducting the experimental task. These data suggest that a referent was retrieved via abstract pointing and that abstract pointing can potentially be used for referent indication in a discourse. We conclude that abstract pointing has a potential communicative function.